Janus kinase inhibitors in pulmonary and extra-pulmonary sarcoidosis: A case series and a systematic review of the literature - Quaggetto, Maxime; Ben salem, Thouraya; Haroche, Julien; Campagne, Julien; Moyon, Quentin; Lhote, Raphael; Amoura, Zahir; Cohen Aubart, Fleur (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Sarcoidosis is an inflammatory granulomatous disease of unknown cause affecting the lungs and frequently extra-thoracic organs. Several immunosuppressive agents have been evaluated in patients refractory to steroids or as steroids-sparing treatments with low level of evidence and conflicting results. JAK inhibitors (JAKi) are novel immunosuppressive agents and recent reports suggested their potential to induce disease response. We report four new sarcoidosis cases treated with JAKi and present a systematic review of the literature. Methods: We describe four new cases and conducted a literature review using Pubmed, Medline, Embase and Cochrane Library. All English-language reports of sarcoidosis patients treated with JAKi published between January 2004 and 2024 were included. Results: We included 4 cases, as well as 45 cases from a systematic review of the literature, reported in 21 articles, leading to a cohort of 49 patients (female 53%, median [IQR 25-75] age 55 [43-60] years). Most cases had pulmonary and cutaneous sarcoidosis, while cardiac and neurological sarcoidosis were less frequent. Indication for JAKi were: steroid sparing agent (29%), refractory disease (22%), non-sarcoidosis indication (10%) and not specified (39%). Most patients received Tofacitinib 5 mg twice daily. Median corticosteroids dosage at treatment initiation was 15 [10-25] mg/day. After a median follow-up of 8 [6-12] months, complete response was achieved in 45% of cases and partial response in 49%, with few adverse events reported. Corticosteroids were discontinued in 11/23 (48%) and reduced in 6/23 (26%). Conclusions: JAK inhibitors appear to be a promising therapeutic option in sarcoidosis patients who are corticosteroid-dependent or refractory to conventional immunosuppressants. Prospective studies are now needed to confirm their efficacy and long-term safety.